6x+4x-45=60-5x

Simple and best practice solution for 6x+4x-45=60-5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+4x-45=60-5x equation:


Simplifying
6x + 4x + -45 = 60 + -5x

Reorder the terms:
-45 + 6x + 4x = 60 + -5x

Combine like terms: 6x + 4x = 10x
-45 + 10x = 60 + -5x

Solving
-45 + 10x = 60 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
-45 + 10x + 5x = 60 + -5x + 5x

Combine like terms: 10x + 5x = 15x
-45 + 15x = 60 + -5x + 5x

Combine like terms: -5x + 5x = 0
-45 + 15x = 60 + 0
-45 + 15x = 60

Add '45' to each side of the equation.
-45 + 45 + 15x = 60 + 45

Combine like terms: -45 + 45 = 0
0 + 15x = 60 + 45
15x = 60 + 45

Combine like terms: 60 + 45 = 105
15x = 105

Divide each side by '15'.
x = 7

Simplifying
x = 7

See similar equations:

| 51-5x=19+11x | | 5r+11-2r-1= | | -23=-6p-7p | | 3z+4=4 | | 0=4.9t^2-11t-92 | | 23x+4(x+1)=27(x+1)-23 | | 4x+3(4x+7)=133 | | 6(9+x)=7x-4 | | 0=-4.9t^2+11t-92 | | 9(10x-1)+1=20 | | -5-7(1+8x)=268 | | 15m-2+4m-17= | | 18v=954 | | 5n=7+3x | | 3x+2(3-x)=9 | | (-6)(-2)(8r)= | | (fg)(x)=(x-8)(4x^2) | | 0=-x^2+100x-2400 | | 2x-1=-x+15 | | 7x-y+18y-4x-15y= | | (2g+7)=(3g-5g+2) | | .5x-24=3x-46 | | -8(x+4)=7(2x+8) | | 68x-60=80 | | 2(5n-3)-n-2= | | 68x-60= | | 8x-13y+5y+x= | | 2p-2+p=-9 | | 24x-4=4 | | -2(5h-4)+10=8 | | 4(y-7)(-y-3)=0 | | x+(x+16)/3=228 |

Equations solver categories